The Influence of Financial Management, Community Participation, Implementation of Good Governance, Supervisionandquality of Humanresources on Village Financial Accountability - SIMANJUTAK, Arthur; SAGALA, Lamria; SAGALA, Farida; GINTING, Mitha Chirstina; SIMANULLANG, Randy Lorenza (Journal of Tourism Economics and Policy, 2023)
This study was conducted to analyze the influence of Financial Management, Community Participation, Implementation of Good Governance, Supervision and Quality of Human Resources on Village Financial Accountability in Siempat Nempu Hulu District, Dairi Regency. This research is quantitative research with associative or causal research. data analysis method in research using SPSS version 26. The results showed partially that Financial Management has a positive and significant effect on village financial accountability, Community Participation has a positive and significant effect on village financial accountability, the implementation of Good Governance has a positive and significant effect on village financial accountability. Meanwhile, supervision has a positive and insignificant effect on village financial accountability and the quality of human resources has a positive and insignificant effect on village financial accountability in Siempat Nempu Hulu District, Dairi Regency.